Advancing psychotherapy and evidence-based psychological interventions - Emmelkamp, Paul M.G.; David, Daniel; Beckers, Tom; Muris, Peter; Cuijpers, Pim; Lutz, Wolfgang; Andersson, Gerhard; Araya, Ricardo; Banos Rivera, Rosa M.; Barkham, Michael; Berking, Matthias; Berger, Thomas; et al. (International journal of methods in psychiatric research, 2014)
Psychological models of mental disorders guide research into psychological and environmental factors that elicit and maintain mental disorders as well as interventions to reduce them. This paper addresses four areas. (1) Psychological models of mental disorders have become increasingly transdiagnostic, focusing on core cognitive endophenotypes of psychopathology from an integrative cognitive psychology perspective rather than offering explanations for unitary mental disorders. It is argued that psychological interventions for mental disorders will increasingly target specific cognitive dysfunctions rather than symptom‐based mental disorders as a result. (2) Psychotherapy research still lacks a comprehensive conceptual framework that brings together the wide variety of findings, models and perspectives. Analysing the state‐of‐the‐art in psychotherapy treatment research, “component analyses” aiming at an optimal identification of core ingredients and the mechanisms of change is highlighted as the core need towards improved efficacy and effectiveness of psychotherapy, and improved translation to routine care. (3) In order to provide more effective psychological interventions to children and adolescents, there is a need to develop new and/or improved psychotherapeutic interventions on the basis of developmental psychopathology research taking into account knowledge of mediators and moderators. Developmental neuroscience research might be instrumental to uncover associated aberrant brain processes in children and adolescents with mental health problems and to better examine mechanisms of their correction by means of psychotherapy and psychological interventions. (4) Psychotherapy research needs to broaden in terms of adoption of large‐scale public health strategies and treatments that can be applied to more patients in a simpler and cost‐effective way. Increased research on efficacy and moderators of Internet‐based treatments and e‐mental health tools (e.g. to support “real time” clinical decision‐making to prevent treatment failure or relapse) might be one promising way forward. Copyright © 2013 John Wiley & Sons, Ltd.